TEACHER TALK IN TEACHING ENGLISH FOR STUDENTS WITH AUTISM SPECTRUM DISORDER (ASD) - Setiadi, Indira Bagus (Universitas Negeri Semarang, 2017)
This research was intended to describe the teacher talk performed by the English teacher when teaching students with Autism Spectrum Disorder (ASD) in inclusive setting. It aimed at classifying the types of direct and indirect teacher talk performed by the teacher, describing the teacher’s perspective toward it, and describing the students’ response toward it. The data gained through observations and interview. The findings of this study showed the teacher employed 3 direct teacher talk; lecturing, giving directions, and criticizing/ justifying authority, and 4 indirect teacher talk; accepting feeling, praising/ encouraging, accepting/ using ideas of students, and asking questions. It revealed that the teacher perceived her talk provide the students eleven function of teacher talk; initiating interaction, comprehending information, stimulating their response, controlling their misbehavior, avoiding confusion, comprehending instructions, motivating participation, encouraging doing good deed, managing activity, raising confident, and keeping enthusiasm. It showed the good use of teacher talk could provide eleven functions to help the students in teaching learning process.